Perennial herb diversity contributes more than annual herb diversity to multifunctionality in dryland ecosystems of North-western China - Guo, Hao; Zhou, Xiao-bing; Tao, Ye; Yin, Jin-fei; Zhang, Lan; Guo, Xing; Liu, Chao-hong; Zhang, Yuan-ming (Frontiers in Plant Science, 2023)
considerable attention has been given to how different aspects of biodiversity sustain ecosystem functions. Herbs are a critical component of the plant community of dryland ecosystems, but the importance of different life form groups of herbs is often overlooked in experiments on biodiversity-ecosystem multifunctionality. Hence, little is known about how the multiple attributes of diversity of different life form groups of herbs affect changes to the multifunctionality of ecosystems. We investigated geographic patterns of herb diversity and ecosystem multifunctionality along a precipitation gradient of 2100 km in Northwest China, and assessed the taxonomic, phylogenetic and functional attributes of different life form groups of herbs on the multifunctionality. We found that subordinate (richness effect) species of annual herbs and dominant (mass ratio effect) species of perennial herbs were crucial for driving multifunctionality. Most importantly, the multiple attributes (taxonomic, phylogenetic and functional) of herb diversity enhanced the multifunctionality. The functional diversity of herbs provided greater explanatory power than did taxonomic and phylogenetic diversity. In addition, the multiple attribute diversity of perennial herbs contributed more than annual herbs to multifunctionality. Our findings provide insights into previously neglected mechanisms by which the diversity of different life form groups of herbs affect ecosystem multifunctionality. These results provide a comprehensive understanding of the relationship between biodiversity and multifunctionality, and will ultimately contribute to multifunctional conservation and restoration programmes in dryland ecosystems.